1973
DOI: 10.1017/s0021859600057105
|View full text |Cite
|
Sign up to set email alerts
|

Studies on genotype × spacing interactions for herbage yield, using a modified diallel analysis

Abstract: Forty-four full-sib families from a diallel cross between 10 Lolium ((multiflorum x perenne) xperenne) clones were planted in the autumn at 0-6 x 0-6 m and 0-lx0-lm spacings. Fresh weight of individual plants was measured on three occasions during the following spring and summer. The analysis of the diallel cross was extended to account for combining ability x spacing interactions, and to estimate between-spacing combining ability correlations and their sampling errors.Family x spacing interactions became incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1974
1974
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…spaced plant yield), r g is the genetic correlation between x and y, and i Using the estimates of efficiency from the recurrent data it appears that all the non-sward densities could effectively be used for selection for sward yield. This is in agreement with the results reported by Sedcole & Clements (1973), although, these authors did not use as high a density as that of the swards. The spaced plants are lower in efficiency than the swards but the higher heritabilities from the row plots make them at least as efficient as the swards.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…spaced plant yield), r g is the genetic correlation between x and y, and i Using the estimates of efficiency from the recurrent data it appears that all the non-sward densities could effectively be used for selection for sward yield. This is in agreement with the results reported by Sedcole & Clements (1973), although, these authors did not use as high a density as that of the swards. The spaced plants are lower in efficiency than the swards but the higher heritabilities from the row plots make them at least as efficient as the swards.…”
Section: Resultssupporting
confidence: 93%
“…England (1967) reported fairly high correlations between yields in broadcast swards and at two other densities (7-5x7-5 cm and 15x15 cm) in Italian ryegrass. Recently Sedcole & Clements (1973) have reported quite high additive genetic correlations for yield in perennial x Italian ryegrass hybrids grown as widely spaced (0-6 x 0-6 m) plants and at a much higher density (0-1 x 0-1 m) comparable with that of a sward. The experiment to be described was carried out to compare three densities for yield assessment in Italian ryegrass.…”
Section: Introductionmentioning
confidence: 99%
“…Copeman and Swift (1966) went on to conclude that the greater variation observed among entries grown as spaced plants made selection using widely spaced plant nurseries preferable. Sedcole and Clements (1973) reported high genetic correlations and similar heritabilities for forage yield between 0.6‐ and 0.1‐m spacing in Lolium multiflorum × L. perenne hybrids. They concluded that selection among widely spaced plants had been unduly criticized and that the ease of planting and maintaining spaced plants made this technique preferable in forage breeding.…”
mentioning
confidence: 80%
“…Testing under sward conditions is usually deferred to the progeny assessment phase but even here, due to restrictions imposed by low seed supplies, the tests are confined to relatively small plot trials . It has long been recognised that there are serious limitations in assessing performance under such restrictive conditions when extrapolating to the performance on the farm (JENKIN, 1931 ;LAZENBY & ROGERS, 1962.1964,1965ENGLAND, 1967 ;WRIGHT & DO VALLE RIBIERO, 1973 ;SEDCOLE & CLEMENTS, 1973) . Thus although LAZENBY (1957) initially showed that the ranking of perennial ryegrass (Lolium perenne) genotypes does not change when evaluated in spaced plants, rows, drills and broadcast plots, later studies (LA-ZENBY & ROGERS, 1965) indicated that spacings of 22 cm or less between plants were necessary for assessing sward yielding ability .…”
Section: Introductionmentioning
confidence: 99%